Every building has a history - Langley, Andrew (Chicago, Illinois Heinemann Library, 2014)
Houses, schools, factories, railway stations we are surrounded by buildings. Most of them look ordinary, yet they may have surprising stories to tell. How and why were they built? Who lived in them? What were their links with other events? And who first found out their history? This book will help you discover these hidden tales for yourself. It explains basic research techniques, and guides you to the best places
A gift from book Africa
Arts
1 2 13
NEW_ZTN_GN
Keywords: Architecture and history -- Juvenile literature; History -- Research -- Juvenile literature